FUNDING AGENCIES CONTRIBUTION ON FINANCIAL MANAGEMENT RESEARCH PUBLICATIONS DURING 2014-2023: A SCIENTOMETRIC STUDY - M, Yasmin; Nair, Chithra s. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Purpose: This study examines trends in financial management research between 2014 and 2023, focusing on funding patterns, citation trends, institutional contributions, and thematic evolution within the field. Methodology: Data was sourced from the Web of Science Core Collection, comprising 51,113 articles on financial management published between 2014 and 2023. The dataset was refined to 8,103 publications based on crucial funding agency mentions. Scientometric analysis was employed to identify global research trends and collaborations, including citation counts, bibliographic coupling, and keyword co-occurrence. Findings: The study reveals a growing concentration of financial management research in China and the USA, with China leading in funding support through the National Natural Science Foundation of China (NSFC). Citation trends show a decline in the impact of individual articles over time, although publication volume has increased. Central themes such as sustainability, corporate governance, and risk management dominate the field, with a noticeable rise in research incorporating technology, particularly blockchain and machine learning. The COVID-19 pandemic influenced the research focus on resilience and public health finance. Notably, interdisciplinary collaboration is rising, especially between finance, technology, and sustainability, with key journals like Sustainability and Journal of Cleaner Production leading the publication output. Originality/Value: This study provides a comprehensive overview of the evolving landscape of financial management research, offering insights into funding influences, citation dynamics, and emerging research themes. The findings highlight the increasing importance of sustainability and technology in financial management and the growing role of global collaboration in shaping future research directions.